(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article is devoted to the topic of socio-psychological aspects of educating future teachers to work on themselves. Also, in the text of the article, issues such as psychological foundations, social psychological determinants, professional motives formed in teachers, tolerance and empathic abilities are widely covered.